Role of stabilin-1 in chronic liver tissue injury and repair. (23rd February 2017) - Shetty, Shishir; Patten, Daniel; Rantakari, Pia; Weston, Chris; Jalkanen, Sirpa; Salmi, Marko; Adams, David
Abstract: Background: Organ fibrosis is a major cause of global mortality. Few medical therapies are available to treat this condition. We have previously demonstrated increased expression of stabilin-1 at sites of chronic liver disease. Using models of chronic liver injury, we aimed to elucidate the role of stabilin-1 during fibrosis and repair. Methods: We used full knockout and cell specific knockouts of stabilin-1 in murine models of chronic liver injury including carbon tetrachloride treatment and a methionine and choline deficient diet. A resolution phase after carbon tetrachloride treatment was used to study tissue repair. Tissue was analysed for fibrosis by confocal microscopy, collagen quantification, and immune cell infiltrate analysis. RNA sequencing and cell transfer experiments were done to elucidate underlying mechanisms. Human tissue was also analysed for stabilin-1 expression in chronic liver injury. Findings: We detected a subset of stabilin-1 macrophages that were induced at sites of cellular injury close to the hepatic scar in mouse models of liver fibrosis and in human liver disease. Stabilin-1 deficiency abrogated malondialdehyde-LDL uptake by hepatic macrophages and was associated with excess collagen III deposition. Mechanistically, the lack of stabilin-1 led to elevated intrahepatic levels of the profibrogenic chemokine CCL3 and an increase in GFAP+ fibrogenic cells. Stabilin-1 knockout macrophages demonstrated a proinflammatory phenotype during liver injury and this led to delayed wound healing. Interpretation: We have demonstrated a pathway in which the evolutionarily conserved receptor stabilin-1 on tissue-infiltrating macrophages promotes the uptake of products of lipid peroxidation and thus prevents excess scarring. We propose that macrophage stabilin-1 is a crucial defence against oxidative tissue damage and thereby maintains tissue homoeostasis. Funding: Wellcome Trust.